On the Use of Fixed‐Intensity Functional Electrical Stimulation for Attenuating Essential Tremor. Issue 11 (17th February 2014) - Bó, Antônio Padilha Lanari; Azevedo‐Coste, Christine; Geny, Christian; Poignet, Philippe; Fattal, Charles
Abstract A great proportion of essential tremor (ET) patients have not so far been able to receive functional benefits from traditional therapies. In this regard, the use of functional electrical stimulation (FES) has been proposed for reducing tremor amplitude by stimulating muscles in antiphase with respect to the trembling motion. Although some studies have reported success in terms of tremor attenuation, drawbacks still exist that prevent the method from being used in real‐life applications. In this article, we explore an alternative approach: a strategy based on the hypothesis that FES‐induced constant muscle contraction may provide functional benefit for tremor patients. To evaluate the proposed strategy, experiments were conducted in which stimulation was intermittently turned on and off while the subjects performed a static motor task. The results of the proposed experimental protocol indicate that tremor attenuation using this strategy is feasible, as consistent tremor attenuation levels were obtained in eight out of 10 ET patients. Nonetheless, tremor reduction was not instantaneous for all successful trials, indicating that prior training with FES may improve the overall response. Furthermore, although simpler assistive devices may potentially be designed based on this technique, some experimental difficulties still exist, which suggests that further studies are necessary.